Experiences of lifestyle changes among Thai older adults six months after applying the Plan-Do-Study-Act (PDSA) cycle - Manothai Wongsala; Sirpa Rosendahl; Els-Marie Anbäcken; Pornpun Manasatchakun; Jessica Holmgren (BMC Geriatrics, 2024)
Abstract Background Thai older adults are valuable resources in their society. The Thai health service system is challenged when it comes to ensuring that older Thai adults can continue to live healthy and independent lives in society. It is of great value to support independence and improve older people’s active ageing. Promoting lifestyle changes by applying the Plan-Do-Study-Act cycle (PDSA cycle), at group meetings in a municipality context, is a way of focusing on active ageing. This study aims to describe older adults´ experiences of lifestyle change six months after finishing group meetings applying the PDSA cycle. Methods A qualitative approach with individual interviews and a qualitative content analysis were used with 12 Thai older adults who participated in the meetings applying the PDSA cycle. Results Six months after finishing applying the PDSA cycle, some older adults kept their individual goals and were influenced by their family surroundings. They also formulated additional goals. Three categories and six sub-categories emerged: Keeping individual goals, influenced by the surroundings, and formulation of additional goals were the overall categories. Conclusions These Thai older adults showed that they had the ability to make lifestyle changes with the support of the PDSA cycle, but not all maintained their planned activities after six months. The question is how healthcare professionals and the surroundings, may further support and motivate these people to maintain these changes based on their own preferences in a sustainable way.